Effect of plot size and precipitation magnitudes on the activation of soil erosion processes using simulated rainfall experiments in vineyards - Neumann, Martin; Kavka, Petr; Devátý, Jan; Stašek, Jakub; Strouhal, Luděk; Tejkl, Adam; Kubínová, Romana; Rodrigo-Comino, Jesús (Frontiers in Environmental Science, 2022)
Soil erosion is recognized as a threat to humankind and to natural ecosystems when sustainable limits are exceeded. Several researchers have used various tools, such as rainfall simulators, to assess extreme rainfall events and non-sustainable soil management practices. However, combinations of two different devices of different sizes has not been tested before, especially in vineyards. The aim is to verify whether plot size, connectivity processes and rainfall distribution affect the activation of soil erosion. In this research on soils cultivated with vineyards in the Moravia Region in the south-eastern part of the Czech Republic, we have performed various rainfall simulation experiments with a small device (1 × 1 m) and with a large device (8 × 1 m). Our results show that the surface runoff was approximately 30% higher on the small plot than on the large plot. The large rainfall simulator produced sediment concentration that was up to 3 times higher, and soil loss that was up to 1.5 times higher, even when the surface runoff was 30%–50% lower for the large rainfall simulator. We therefore conclude that there is a clear influence of surface length and plot size on surface runoff, soil loss and sediment concentration activation. When planning their experiments, researchers need to consider that the type of device can have a drastic influence on the final results. Two devices subjected to the same rainfall intensity (60 mm h−1) can produce very different results, e.g., depending on plot size and kinetic energy. Our results can be effectively used to plan soil protection measures and to inform local authorities about areas prone to flooding and about loss of sediments.